Determinants of improved quality of life among older adults with multimorbidity receiving integrated outpatient services: A hospital-based retrospective cohort study. (November 2021) - Yen, Ko-Han; Hsu, Chia-Chia; Yu, Pei-Chin; Liu, Hsin-Yu; Chen, Zhi-Jun; Chen, Yu-Wen; Peng, Li-Ning; Lin, Ming-Hsien; Chen, Liang-Kung
Highlights: Integrated outpatient services improved the quality of life of older adults with multimorbidity. Those with poorer nutritional status, depressive symptoms and frailty were less likely to show improvement in their quality of life. A harmonized care plan covering chronic condition management and functional enablement may be the optimal model for older adults with multimorbidity. Abstract: Background: Older adults with multiple complex care needs tend to receive fragmented care that may jeopardize their quality of life (QoL) and health outcomes. This study evaluated the determinants of improved QoL among integrated outpatient service recipients with multimorbidity. Methods: We conducted a retrospective cohort study of integrated geriatric outpatient services (IGOS) at a tertiary medical center in Taiwan. Data from 2018 to 2019 were retrieved. All patients underwent comprehensive geriatric assessment, which included demographic information, serial functional assessments, and assessment for QoL. QoL was reassessed through a telephone survey 6 months after the patients' first visit to IGOS. Factors associated with the interval changes in QoL were identified using multivariate logistic regression. Results: Data from 995 patients receiving IGOS (mean age: 82.21 ± 7.96 years, 54.5% males) were analyzed. An overall mean improvement in QoL was noted (EQ-5D index: +0.055±0.26, p <0.001) while 747 recipients reported maintained or improved QoL. The results of the multivariate logistic regression showed that poorer nutritional status (OR = 1.56, 95% CI: 1.07–2.28), depressive symptoms (OR = 1.99, 95% CI: 1.38–2.86), and frailty (OR = 1.66, 95% CI: 1.10–2.52) were independent risk factors for poorer QoL after adjustment for baseline QoL. Conclusions: Integrated outpatient services improved the quality of life of older adults with multimorbidity. Those with poorer nutritional status, depressive symptoms and frailty were less likely to show improvement in their QoL.